The Role of Anesthesiology in Global Health : A Comprehensive Guide - Roth, Ram; Frost, Elizabeth A.M; Gevirtz, Clifford; Atcheson, Carrie L.H (Springer International Publishing : Imprint: Springer, 2015)
"This brilliantly assembled expert compendium provides a much-needed guide for the practical application of anesthesiology in medical practice in the most bereft underdeveloped and violence-afflicted regions of the globe." -Seymour Topping, Professor Emeritus of International Journalism, Columbia University   This is a comprehensive guide to the role of anesthesiologists in medical missions. In their capacity as perioperative physicians, anesthesiologists improve the safety and efficacy of surgical interventions for underserved patients in low- and middle-income countries around the world. Contributions from international experts in global health provide essential historical context, practical medical and surgical considerations for planning missions, and scenarios of "on the ground" implementation of care. The final section considers anesthesiology education in the context of global health. This is an encompassing and eye-opening resource for trainees and physicians considering participating in a medical mission and students and faculty of global health.